2010
DOI: 10.1186/1744-8069-6-32
|View full text |Cite
|
Sign up to set email alerts
|

The val158met Polymorphism of Human Catechol-O-Methyltransferase (COMT) Affects Anterior Cingulate Cortex Activation in Response to Painful Laser Stimulation

Abstract: BackgroundPain is a complex experience with sensory, emotional and cognitive aspects. Genetic and environmental factors contribute to pain-related phenotypes such as chronic pain states. Genetic variations in the gene coding for catechol-O-methyltransferase (COMT) have been suggested to affect clinical and experimental pain-related phenotypes including regional μ-opioid system responses to painful stimulation as measured by ligand-PET (positron emission tomography). The functional val158met single nucleotide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 53 publications
(96 reference statements)
3
21
0
1
Order By: Relevance
“…Second, COMT plays a role in reward and punishment (Tunbridge et al, 2006), making it an intuitive choice for the study of normative pressure, because social disapproval can serve as a powerful aversive stimulus in operant conditioning. Indeed, a previous study demonstrated higher ACC activation in response to painful stimuli for homozygous Met-allele carriers (Mobascher et al, 2010). In addition, an fMRI study by Klucharev et al (2009) found neuroimaging evidence that reinforcement learning signals are relevant for conformist behavior.…”
Section: Introductionmentioning
confidence: 89%
“…Second, COMT plays a role in reward and punishment (Tunbridge et al, 2006), making it an intuitive choice for the study of normative pressure, because social disapproval can serve as a powerful aversive stimulus in operant conditioning. Indeed, a previous study demonstrated higher ACC activation in response to painful stimuli for homozygous Met-allele carriers (Mobascher et al, 2010). In addition, an fMRI study by Klucharev et al (2009) found neuroimaging evidence that reinforcement learning signals are relevant for conformist behavior.…”
Section: Introductionmentioning
confidence: 89%
“…The met158 allele is associated with higher subjective and brain responses to pain (Mobascher et al, 2010) and suppressed MOR response to pain (Zubieta et al, 2003). Whether the COMT met158 allele influences alcohol dependence remains unclear.…”
Section: Genetic Influences On Pain Alcohol Analgesia and Alcoholmentioning
confidence: 99%
“…14 Furthermore, functional variants in the COMT gene that reduce COMT activity 13,15,16 are associated with increased susceptibility to FM, 17-21 TMD 22 and experimental pain 22,23 as well as impaired response to treatment. 24,25 It is estimated, based on the frequency of allele variation, that nearly two-thirds of patients with chronic pain disorders possess the low-activity COMT variants. 26,27 …”
Section: Introductionmentioning
confidence: 99%